Ascomycetes associated to angiosperms in the cloud forest of central Veracruz, Mexico - Medel-Ortiz, Rosario; Lorea-Hernández, Francisco Gerardo; Baeza Guzmán, Yajaira; Palestina-Villa, Elvia Naara; Belingheri Lagunes, Maria Emilia (Instituto de Ecología, A.C., 2019)
Background and Aims: Little is known about ascomycete fungi associated with angiosperms that inhabit cloud forest in Mexico. Hence, the aim of this work is to contribute to the knowledge of ascomycete diversity in this kind of forest in the state of Veracruz, Mexico.Methods: Opportunistic sampling was carried out in five localities with cloud forest fragments in the municipalities of Coatepec, San Andrés Tlalnelhuayocan and Xalapa. Specimens were studied macro and microscopically following routine techniques in order to identify them with specialized literature. Whenever possible the host on which the fungi were growing was identified.Key results: We found 13 species of ascomycete fungi belonging to the orders Diaporthales (family Gnomoniaceae), Helotiales (Dermateaceae, Helotiaceae), Hypocreales (Bionectriaceae, Niessliaceae), Orbiliales (Orbiliaceae) and Pleosporales (Massarinaceae, Montagnulaceae). Seven of the studied species are new records for Mexico, two are new for Veracruz, one corresponds to an undescribed species and three species are previously acknowledged records in this type of forest, but their descriptions are amended. Hydropisphaera suffulta was found growing naturally with its anamorph Acremonium sp. We also report a case of mycoparasitism between the genera Letendraea helminthicola and Helminthosporium velutinum. The species here discussed were found growing on individuals of the families Altingiaceae (Liquidambar styraciflua), Boraginaceae (Varronia sp.), Fabaceae (Inga inicuil), Fagaceae (Quercus sp.), Piperaceae (Piper spp.), and four on unidentified wood.Conclusions: The cloud forest is an important reservoir of the diversity of ascomycete fungi in Mexico and, in this case, for Veracruz state. In this study we report species of the families Montagnulaceae and Niessliaceae, that until now had not been recorded in this type of vegetation. Furthermore, we found seven species that are new records for Mexico, and two more for Veracruz, and an apparently undescribed species of the genus Belonopsis is registered.